The A756T Mutation of the ERG11 Gene Associated With Resistance to Itraconazole in Candida Krusei Isolated From Mycotic Mastitis of Cows - Du, Jun; Ma, Wenshuang; Fan, Jiaqi; Liu, Xiaoming; Wang, Yujiong; Zhou, Xuezhang (Frontiers in Veterinary Science, 2021)
Candida krusei (C. krusei) has been recently recognized as an important pathogen involved in mycotic mastitis of cows. The phenotypic and molecular characteristics of 15 C. krusei clinical isolates collected from cows with clinical mastitis in three herds of Yinchuan, Ningxia, were identified by matrix-assisted laser desorption ionization–time of flight mass spectrometry. In addition to sequencing analysis, the ERG11 gene that encodes 14α-demethylases, the expression of the ERG11 gene, and efflux transporters ABC1 and ABC2 in itraconazole-susceptible (S), itraconazole-susceptible dose dependent (SDD), and itraconazole-resistant (R) C. krusei isolates was also quantified by a quantitative real-time reverse transcription polymerase chain reaction (qRT-PCR) assay. Sequencing analysis revealed three synonymous codon substitutions of the ERG11 gene including T939C, A756T, and T642C in these C. krusei clinical isolates. Among them, T642C and T939C mutations were detected in itraconazole-resistant and -susceptible C. krusei isolates, but the A756T substitution was found only in itraconazole-resistant isolates. Importantly, the expression of the ERG11 gene in itraconazole-resistant isolates was significantly higher compared with itraconazole-SDD and itraconazole-susceptible isolates (p = 0.052 and p = 0.012, respectively), as determined by the qRT-PCR assay. Interestingly, the expression of the ABC2 gene was also significantly higher in itraconazole-resistant isolates relative to the itraconazole-SDD and itraconazole-susceptible strains. Notably, the expression of ERG11 was positively associated with resistance to itraconazole (p = 0.4177 in SDD compared with S, p = 0.0107 in SDD with R, and p = 0.0035 in S with R, respectively). These data demonstrated that mutations of the ERG11 gene were involved in drug resistance in C. krusei. The A756T synonymous codon substitution of the ERG11 gene was correlated with an increased expression of drug-resistant genes including ERG11 and ABC2 in itraconazole-resistant C. krusei isolates examined in this study.